"Is Irish Stew the only kind of stew we can afford to make, mother?" The history of a recipe. (3rd July 2021) - Cashman, Dorothy; Farrelly, John
ABSTRACT: This paper traces the social, political and culinary history of Irish stew from what are its earliest iterations through to its inclusion in a recently published collection of Irish recipes. The constituent ingredients are contextualized and the emergence of oral and printed recipes tracked within a theoretical framework that gives equal importance to the political and social contexts that existed as successive recipes for the dish gained currency. The shifts in meanings and associations of the dish among different people – those who observed and commented on the Irish, and the Irish themselves – are traced, detailing its emergence from painful association with subsistence living to a confident place in the pantheon of Irish cuisine – an important part of Ireland's intangible cultural heritage.